The Effect of Levers of Control System on Sustainability Performance: Evidence from Indonesian Batik Industry - Christiyaningsih Budiwati; Mazlina Mustopha; Ong Tse San; Ridzwana Mohd Said (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2025)
Small and Medium Enterprises (SMEs) are significant contributors to the world’s economy, particularly in times of crisis. SMEs also constitute an integral part of Indonesia's self-sustaining economic system and hold considerable promise for enhancing societal well-being. One of the SMEs that plays a big role in the Indonesian economy is the batik industry. However, with the development of fashion and modernization, batik clothing faces challenges to survive. The purpose of this study is to examine the effect of four levers of management control systems on sustainability performance. The Indonesian batik industry was chosen as the object of this study. Information was collected through a survey of batik makers throughout Indonesia. The result from the survey shows that four levers of the management control system positively affect sustainability performance.